2018
DOI: 10.1038/s41375-018-0122-0
|View full text |Cite|
|
Sign up to set email alerts
|

Novel evidence that extracellular nucleotides and purinergic signaling induce innate immunity-mediated mobilization of hematopoietic stem/progenitor cells

Abstract: Pharmacological mobilization of hematopoietic stem progenitor cells (HSPCs) from bone marrow (BM) into peripheral blood (PB) is a result of mobilizing agent-induced “sterile inflammation” in the BM microenvironment due to complement cascade (ComC) activation. Here we provide evidence that ATP, as an extracellular nucleotide secreted in a pannexin-1-dependent manner from BM cells, triggers activation of the ComC and initiates the mobilization process. This process is augmented in a P2X7 receptor-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(116 citation statements)
references
References 63 publications
7
109
0
Order By: Relevance
“…of tumors by catalyzing the formation of ADO, which is an immunosuppressive medium [98]. Studies have shown that high expression of CD73 is associated with both immunosuppression and poor prognosis in patients with NSCLC [98][99][100]. Therefore, understanding the crosstalk between CD73, ADO and TME is an area of active research, as described below (Fig.…”
Section: Cell Surface Molecules and Selected Soluble Factorsmentioning
confidence: 99%
“…of tumors by catalyzing the formation of ADO, which is an immunosuppressive medium [98]. Studies have shown that high expression of CD73 is associated with both immunosuppression and poor prognosis in patients with NSCLC [98][99][100]. Therefore, understanding the crosstalk between CD73, ADO and TME is an area of active research, as described below (Fig.…”
Section: Cell Surface Molecules and Selected Soluble Factorsmentioning
confidence: 99%
“…This pattern of activation correlates with diurnal fluctuations in the level of the bioactive phosphosphingolipid sphingosine-1-phosphate in PB, which is a potent chemoattractant for HSPCs and mediates their egress from BM into the circulation [8,14]. Recent evidence from our laboratories indicates that an important role in triggering stress-related or pharmacological mobilization of HSPCs is played by extracellular adenosine triphosphate (ATP), a crucial mediator of the purinergic signaling network [15][16][17]. ATP is released from activated or stressed cells, as seen during hypoxia or after administration of pro-mobilizing agents, and activates the Nlrp3 inflammasome protein complex in innate immunity cells by engaging the P2X7 purinergic receptor on the cell surface [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 93%
“…Additional plasma was collected for colorimetric assays. For SKL, CFU-GM, VSEL, MSC, and EPC analysis, blood was collected from the vena cava (with a 25gauge needle and 1-ml syringe containing 250 U heparin) [15,17].…”
Section: Peripheral Blood Parametersmentioning
confidence: 99%
See 2 more Smart Citations